Implementation and Development of School Work Plans (RKS) and School Activity Budget Plans (RKAS) - Wahyuni, Sri; Cahyono, A Dimas Sugra; Marsih, Marsih; Murniati, Ngurah Ayu Nyoman (Papanda Publisher, 2025)
Planning is a fundamental aspect in educational management. In the context of schools, the School Work Plan (RKS) and the School Activity and Budget Plan (RKAS) function as strategic and operational guidelines to achieve educational goals. This article aims to describe the definition, legal basis, process of compiling, implementing, and developing RKS and RKAS at SDN Dukuh, Pekalongan City. The study used a qualitative approach. Data sources from primary data and secondary data. The results of the study stated that in planning RKS and RKAS at SDN Dukuh, Pekalongan City, the principles of (1) participation, (2) data-based, (3) integration and linkages between objectives, programs, and budgets, (4) transparency and accountability, and (5) suitability to the real needs of the school were considered. Meanwhile, at the implementation and development stage, several things were done, namely: (1) implementation of school programs, (2) monitoring and evaluation, (3) utilization of technology (e-RKAS), and (4) resolution of obstacles and challenges. With the planning and implementation of RKS and RKAS at SDN Dukuh which has applied the appropriate principles, SDN Dukuh has become a quality school, especially in managing the school budget. From the results of the study, it is recommended that schools strengthen the capacity of the planning team, especially in understanding and using quality data as a basis for planning.